2018
DOI: 10.3390/ijms19103020
|View full text |Cite
|
Sign up to set email alerts
|

Protein Quality Control in the Endoplasmic Reticulum and Cancer

Abstract: The endoplasmic reticulum (ER) is an essential compartment of the biosynthesis, folding, assembly, and trafficking of secretory and transmembrane proteins, and consequently, eukaryotic cells possess specialized machineries to ensure that the ER enables the proteins to acquire adequate folding and maturation for maintaining protein homeostasis, a process which is termed proteostasis. However, a large variety of physiological and pathological perturbations lead to the accumulation of misfolded proteins in the ER… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
51
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(51 citation statements)
references
References 266 publications
(340 reference statements)
0
51
0
Order By: Relevance
“…However, GO analysis revealed that transcriptional response to Tranilast and Amphotericin B shares suppression of several cisplatin resistance pathways including DNA repair (28), antiapoptotic NFKB signaling (25) and protein quality control (27). In addition to these mechanisms, we noted that both drugs reduced expression of autophagy genes.…”
Section: Resistance Of Tumors To Chemotherapy Represents An Importantmentioning
confidence: 75%
See 2 more Smart Citations
“…However, GO analysis revealed that transcriptional response to Tranilast and Amphotericin B shares suppression of several cisplatin resistance pathways including DNA repair (28), antiapoptotic NFKB signaling (25) and protein quality control (27). In addition to these mechanisms, we noted that both drugs reduced expression of autophagy genes.…”
Section: Resistance Of Tumors To Chemotherapy Represents An Importantmentioning
confidence: 75%
“…Using a synthetic lethality screening we revealed and validated 3 hits, which significantly reduced ATP7B-mediated tolerance to cisplatin in ovarian cancer cells. The drugs acted via blocking ATP7B export from the Golgi and down-regulating large cohorts of genes, which belong to cisplatin-resistance pathways including DNA repair, quality control and autophagy (25)(26)(27)(28). Our findings underscore the effectiveness of unbiased screening approach for drug repurposing studies and pinpoint bio-safe drug candidates to combat ATP7B-mediated resistance of tumors to cisplatin.…”
Section: Introductionmentioning
confidence: 71%
See 1 more Smart Citation
“…Increasing evidence links ER stress to the development of chronic human diseases, such as type 2 diabetes mellitus, NAFLD, neurodegeneration and cancer [1][2][3]. However, the mechanisms whereby ER stress leads to the pathogenesis of various human diseases is incompletely understood.…”
Section: Discussionmentioning
confidence: 99%
“…The endoplasmic reticulum (ER) serves several critical cellular functions, including Ca2+ storage, lipid synthesis and the folding of protein molecules destined for the secretory pathway. Impaired ER function or ER stress has been implicated in a increasing number of chronic human diseases, including obesity, diabetes, neurodegeneration, non-alcohol fatty liver disease (NAFLD) and cancer [1][2][3]. ER stress is an abnormal homeotic condition characterized by the accumulation of unfolded or misfolded proteins in the ER lumen [4].…”
Section: Introductionmentioning
confidence: 99%